Laparoscopic ovariectomy in guinea pigs: A pilot study. (29th May 2019) - McCready, Julianne; Beaufrère, Hugues; Singh, Ameet; Oblak, Michelle; Sanchez, Andrea
Abstract: Objective: To assess the feasibility and safety of laparoscopic ovariectomy in guinea pigs utilizing 3‐mm minilaparoscopic instruments. Study design: Experimental pilot study. Animals: Guinea pigs (n = 3). Methods: The guinea pigs were sedated, placed under general anesthesia, and intubated under endoscopic visualization. A 3‐port technique was used with a 3.9‐mm cannula for the endoscope and two 3.5‐mm cannulas accommodating 3‐mm endoscopic instruments including a 3‐mm vessel sealing device, grasping forceps, and endoscopic scissors. The abdomen was insufflated with CO2 to a pressure of 6–8 mm Hg. The guinea pigs were manually tilted 90° laterally to visualize the dorsally positioned ovaries. Results: The procedure was successfully performed in all 3 animals. The surgery times were 120, 45, 45 minutes for the 3 guinea pigs, and anesthesia times were 186, 90, and 76 minutes, respectively. Placing the animals in complete lateral recumbency was found to be critical to visualize and manipulate the ovaries. The guinea pigs recovered smoothly from anesthesia. Conclusion: Laparoscopic ovariectomy with 3‐mm minilaparoscopic instrumentation using a 3‐port technique was feasible in guinea pigs. Clinical significance: Laparoscopic ovariectomy can be considered as an alternative to open ovariectomy as an elective surgical technique to prevent reproductive disorders in guinea pigs.